واقع التسويق الزراعي في الساحل السوري وأفاق تطويره - محمود, يوسف; يعقوب, غسان; اسما عيل, عدنان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث واقع التسويق الزراعي في الساحل السوري، حيث يستعرض آلية تسويق المحاصيل الرئيسة المزروعة (الحمضيات – البندورة.......). ويتطرق إلى الإجراءات والخطوات التي قامت بها الحكومة السورية على المستويين الداخلي والخارجي لدعم عملية التسويق الزراعي وفعالية هذه الإجراءات وانعكاساتها على العملية التسويقية، كما تحاول الدراسة إلقاء الضوء على ابرز العقبات والمشكلات التي تعترض عملية التسويق الزراعي في الساحل السوري، وفي النهاية تخلص الدراسة إلى ضرورة وضع استراتيجية محددة ومتكاملة من اجل إعادة هيكلية عمل التسويق الزراعي في ضوء المتغيرات الراهنة حيث تبدأ العملية قبل عمل الإنتاج وتنتهي مع وصول المنتج إلى المستهلك النهائي. The study deals with status of farming marketing in the Syrian Coast, showing the mechanism of marketing of the main products ( Sours, Tomato …. etc ), stating the steps and procdures of the Syrian Government at internal and external levels to support the process of farm marketing and the efficiency of these procedures and its reflections on marketing process. The study throws light on the obstacles and problems in the Syrian Coast. Finally, the study reaches the conclusion that It is necessary to put an integral limited strategy for re-structuse farm marketiing in the light of outstanding changes. This process starts before production and ends with the arrival of the commodity to the end-consumer.